PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, LEVERAGE, KEPEMILIKAN MANAJERIAL DAN CAPITAL INTENSITY RATIO TERHADAP TAX AVOIDANCE - Ledya Akmal Syaflet Bandaro; Stefanus Ariyanto (Universitas Multimedia Nusantara, 2020)
This research aims to study the factors affecting Effective Tax Rate as a ratio indicates the efficiency of tax burden management by companies. The factors are Return on Assets (ROA), Ukuran Perusahaan (SIZE), Leverage (LEV), Managerial Ownership (KPM) dan Capital Intensity Ratio (CIR). Research sample were taken from the population of public manufacturing companies in Indonesia for the period 2016-2018, selected with predetermined criteria, resulting 55 companies from the population. The data is analysed using linear regression technique. This research reveals that the only variable that has significant influence towards Effective Tax Rate is Return on Assets and all the variables are simultaneously have effect towards Effective Tax Rate. Keywords: Return on Assets, leverage ratio, Firm Size, Managerial Ownership, Capital intensity, tax avoidance, effective tax rate.